Bank Syariah Sebagai Alternatif - Sudjana, Adang (Bina Nusantara University, 2003)
The principle of not allowing interest practices (riba) has saved the Syariah Bank and their customers from the effects of monetary crisis. In view of Islamic Principles, interest is forbidden. Therefore, all transactions of syariah banking are based on sale-purchase pattern. Besides, all good banking aspects as applied in conventional banking such as, 5 Cs (capital, collateral, capacity, character, and condition) are also applied properly in the line of ukhrawi aspects in managing fund of syariah banking.Â The practice of â€œmark-upâ€ in project funded by syariah bank seems to be very difficult.